The 15-Year Shadow: Borderline Lepromatous Leprosy with Erythema Nodosum Leprosum Following Prolonged Treatment Default - Rendra Darmasatria; Tutty Ariani; Yosse Rizal; Rina Gustia; Irdawaty Izrul (HM Publisher, 2025)
Background: Leprosy, caused by Mycobacterium leprae, persists as a global health issue where the primary challenges are not merely microbial but are deeply rooted in delayed diagnosis and poor treatment adherence. These delays, often driven by profound social stigma, lead to progressive, irreversible disability and sustain community transmission. Erythema Nodosum Leprosum (ENL), an acute immunological complication, further devastates patients' quality of life and complicates management. Case presentation: A 53-year-old Indonesian farmer presented with a 15-year history of untreated leprosy, a journey of neglect initiated by fear of treatment side effects and community ostracism. Clinical examination revealed advanced borderline lepromatous (BL) leprosy with diffuse skin infiltration, multiple anesthetic plaques, and thickened, tender peripheral nerves. He had established WHO Grade 1 disability, characterized by significant sensory loss in his hands and feet and early intrinsic muscle atrophy. A slit-skin smear confirmed a bacteriological index of +3 with a morphological index of 5%, indicating a high load of viable bacilli. Histopathology confirmed BL leprosy with a concurrent mild ENL reaction. A comprehensive, patient-centered management plan was initiated, including a 12-month course of multidrug therapy (MDT-MB), adjunctive care, and intensive counseling. Conclusion: This case powerfully illustrates the